ANALISIS KEMAMPUAN MENULIS KARANGAN DESKRIPSI DALAM BAHASA INDONESIA MELALUI MEDIA GAMBAR SERI PADA SISWA KELAS VII SMP N 18 LAU KABUPATEN MAROS - Aswan, Naki; Nurhayati, Nurhayati; Pammu, Abidin (JURNAL ILMU BUDAYA, 2018)
This study aims, namely (1) describes the ability to write essay description of the class VII SMP Negeri 18 Lau through the use of media image series and (2) to analyze the obstacles faced by students of class VII SMP Negeri 18 Lau in arranging a bouquet of descriptions using the media picture series.This research is a qualitative research. This research data in the form of bouquets description seventh grade students of SMP Negeri 18 Lau. Data collection methods are methods refer to Technical note. Data were analyzed with descriptive methods.The results showed that the analysis of the ability to write essay description of the class VII SMP Negeri 18 Lau through the use of media image series shows (1) the ability to organize ideas in an integrated manner, (2) choice of words / diction precise, (3) the use of vocabulary in varied, (4) the creation of cohesion and coherence and (5) writing techniques in accordance with Indonesian enhanced spelling (EYD). The constraints in the use of media such images in learning, from the point of view of teachers that (a) some teachers still use traditional learning methods, (b) the limited ability of teachers to provide media images in accordance with the concept of learning and (c) the teacher has not been able to use media image series of continuous learning. As from the student's perspective (a) The student has not mastered the rules of spelling properly, (b) students are less serious about work and (c) the influence of the local language diversity.